Improving Posthospital Discharge Telephone Reach Rates Through Prehospital Discharge Face-to-Face Meetings. Issue 6 (November 2017) - Vergara, Franz H.; Sheridan, Daniel J.; Sullivan, Nancy J.; Budhathoki, Chakra
Abstract : Purpose of the Study: The purpose of this study was to determine whether a face-to-face meeting with patients by a telephonic case manager prehospital discharge would result in increased telephone follow-up (TFU) reach rates posthospital discharge. Primary Practice Setting: Acute care adult medicine inpatient units. Methodology and Sample: A quasiexperimental design was utilized. Two adult inpatient medicine units were selected as the intervention and comparison groups. The framework of the study is the transitions theory. A convenience sampling technique was used, whereby 88 eligible patients on the intervention unit received face-to-face meetings prehospital discharge whereas 123 patients on the comparison unit received standard care (no face-to-face meetings). Cross-tabulation and chi-square tests were employed to examine the association of face-to-face meeting intervention and TFU reach rates. Results: Implementing brief (<10 min) face-to-face meetings by a telephonic case manager prehospital discharge resulted in a TFU reach rate of 87% on the intervention unit, whereas the comparison unit only had a 58% TFU reach rate ( p < .001). Implications for Case Management Practice: Increasing reach rates by a telephonic case manager facilitates communication with more patients posthospital discharge. A brief prehospital discharge face-to-face meeting with patients assisted them to understand the reasons for a posthospital discharge telephone call, identified the best times to call using accurate telephone numbers, and taught patients how best to prepare for the call. In addition, by meeting patients face-to-face, the telephonic case manager was no longer an unknown person on the telephone asking them questions about their medical condition. These factors combined may have significantly helped to increase TFU reach rates.